Traditional Chinese Medicine for childhood obesity: an umbrella review of systematic reviews and meta-analyses - He, Yuanyuan; Zhuang, Shixin; Zhussupova, Zhanna; Mussin, Nadiar M.; Zhang, Yiqun; Yu, Jian; Tamadon, Amin (Frontiers in Medicine, 2025)
BackgroundChildhood obesity is a major global public health concern associated with adverse cardiometabolic outcomes and long-term health risks. While conventional treatments such as diet, exercise, and behavioral therapy remain the cornerstone of management, their long-term effectiveness is often limited. Traditional Chinese Medicine (TCM) has been increasingly investigated as an adjunctive approach for pediatric obesity, yet findings from systematic reviews remain fragmented and overlapping.ObjectiveThis umbrella review aimed to synthesize and critically appraise evidence from systematic reviews and meta-analyses (SRs/MAs) evaluating TCM interventions for childhood obesity, assess methodological quality, and quantify evidence overlap.MethodsA systematic search of PubMed, Web of Science, and Scopus was conducted from inception to August 30, 2025. Eligible SRs/MAs included randomized controlled trials (RCTs) or controlled clinical trials of TCM interventions in children and adolescents (<19 years) with obesity or overweight. Two reviewers independently screened studies, extracted data, and assessed methodological quality using AMSTAR-2. Findings were summarized qualitatively by intervention category (herbal medicine, acupuncture/moxibustion, acupressure/massage/cupping, dietary therapy/exercise). Evidence overlap was analyzed using the Corrected Covered Area (CCA).ResultsOf 15 records identified, three SRs/MAs met inclusion criteria encompassing 68 unique primary trials. Herbal medicine significantly reduced BMI and body weight compared with lifestyle interventions. Acupuncture and moxibustion improved BMI, weight, waist circumference, total cholesterol, LDL-C, fasting glucose, and TCM syndrome scores, with body acupuncture outperforming auricular acupuncture. Cupping combined with acupressure was the top-ranked therapy for BMI and weight reduction, while chuna massage demonstrated moderate benefits. No serious adverse events were reported across reviews. Methodological quality was rated as moderate or low. Evidence overlap was moderate-to-high.ConclusionTCM interventions, particularly acupuncture, moxibustion, herbal medicine, and combined physical modalities, appear effective and safe adjuncts for childhood obesity. However, methodological limitations, evidence overlap, and lack of long-term data underscore the need for rigorously designed multicenter RCTs to confirm sustained benefits.Systematic review registrationhttps://archive.org/details/osf-registrations-vnjbw-v1.